FI-Extending Semimodule and Singularity - Alhashemi, Samah; Alhossaini, Asaad M. A. (Iraqi Journal of Science, 2022)
The main aim of this research is to present and to study several basic characteristics of the idea of FI-extending semimodules. The semimodule  is said to be an FI-extending semimodule if each fully invariant subsemimodule of  is essential in direct summand of . The behavior of the FI-extending semimodule with respect to direct summands as well as the direct sum is considered. In addition, the relationship between the singularity and FI-extending semimodule has been studied and investigated. Finally  extending propertywhich is stronger than FI extending,  that  has some results related to FI-extending and singularity is also investigated.